Evaluasi Kegiatan Posyandu di Kelurahan Ancol Kecamatan Pademangan Jakarta Utara - Hadiyanto; Perdana, Putu Bagus Aditya Adi; Rahardja, Felicia Faustina; Wangsaputri, Rafaelle Thalya; Eriady, Angely Margaretha; Vanya Laura Andini; Juan Andre Kuistono (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
The posyandu program evaluation was conducted in RW 04 and 05, Ancol Subdistrict. This program aimed to assess whether the implementation of posyandu activities met established standards, as well as to gather community feedback to improve participation. It also sought to examine the relationship between posyandu attendance frequency, exclusive breastfeeding during the first six months, and knowledge of complementary feeding (MPASI) with the growth of infants and toddlers in the area. The evaluation was carried out through direct observation and interviews with both posyandu cadres and participants. The findings indicated that the implementation of posyandu in RW 04 and 05 generally met the standards; however, feedback highlighted issues related to infrastructure, queuing systems, and variation of counseling materials. Furthermore, the data revealed that many parents tend to bring their children to posyandu only when growth problems are suspected, and that mothers’ knowledge of complementary feeding does not always align with their actual practices.